Analisis Kebijakan Desentralisasi Pendidikan Indonesia - Rizki Erdayani; Muslim Afandi; Syed Agung Afandi (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
This study aims to analyze the bibliometrics and content of Indonesian education decentralization. This study used a qualitative approach with bibliometric and content analysis methods. Research data was obtained from Google Scholar using Publish or Perish. The results of this study indicate that the study of the decentralization of education in Indonesia has fluctuated. In the 2012–2022 period, there were 90 papers, and they were cited 231 times. The highest publication was in 2019, while the lowest was in 2020. There are a total of 115 keywords, 22 clusters, 1137 total link strengths, and 362 occurrences. Indonesia's education decentralization policy is one of the impacts of post-reform governance changes in 1998. In practice, the authority in the education sector in Indonesia is currently not only in the hands of the central government but also of local governments and educational institutions as implementing units. Thus, in Indonesia, regional governments and educational institutions have the flexibility to manage education according to the laws and their respective potentials.